Pengembangan Sistem Informasi Layanan Pemeriksaan Kesehatan Tenaga Kerja Dengan Metode Rational Unified Process (Studi Kasus Klinik Argaraya Medika Malang) - Alfan Babtista Yordan; Yusi Tyroni Mursityo; Djoko Pramono (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Malang, one of the regions in East Java that contributes the highest number of migrant workers in Indonesia can be an advantage for the Argaraya Medika Clinic in developing business and labor inspection services. However, the large number of patients who register for the health check-up of workers every hour of service makes it difficult for officers to handle the inspection files and queue of patients. The registration process of patients that takes a long time because it is done twice on the frontoffice and polyclinic causes the length of the queue. Another problem that is faced is the easy loss of the old data checking and data recording form files. Based on these problems the solution that can be applied is to develop an information system for labor inspection services that can help the patient registration process, check the inspection work, store inspection data, and help the recording of inspection data. The system was developed using the Rational Unified Process (RUP) method with the stages of inception, elaboration, construction, and transition phases. The labor health inspection service information system has been implemented with the results of validation testing to test the system's functionalities with 100% valid results and compability testing to test non-functional requirements resulting in 2 critical issues in 2 browser applications. User Acceptance testing is carried out with seven correspondents from each user indicating that the information system of labor inspection services is well received by the user.